Unfixing the Frame: Visualizing Histories of Transcultural Contact, Exchange & Performance in Prince Roland Bonaparte’s Peaux-Rouges (1884) - Emily L. Voelker (Transatlantica)
This article analyzes the photographic album Peaux-Rouges compiled by Prince Roland Bonaparte in 1884. This album focuses on a troupe of visiting Umonhon (Omaha) Indians in Paris and presents them through tribally specific history and memory. Created within the emergent discourses of nineteenth-century French anthropology grounded in notions of the racial type, the volume has largely been contextualized in these conceptions of human difference and developing scientific cultures. Here, however, the author shifts focus to the experiences of the pictured sitters, examining the photographic exchange embodied in the work as a specific moment in ongoing settler colonial relationships between the Umonhon and European, followed by Euro-American, colonizers. The text explores how local Umonhon meanings related to these pictures intersect with, and complicate, the discourses surrounding their initial making in cosmopolitan networks in Paris. This reading argues that visual references to transcultural exchange and performance in Peaux-Rouges, as well as the material circulation histories of the included photographs over time, disrupt its initial framing based on presumptions of fixed, racial identity.